Association of Mitral Annulus Calcification with High-Sensitivity C-Reactive Protein, Which Is a Marker of Inflammation - Ertuğrul Kurtoğlu; Hasan Korkmaz; Erdal Aktürk; Mücahid Yılmaz; Yakup Altaş; Ahmet Uçkan (Mediators of Inflammation)
Objectives. There are limited clinical data revealing the relationship between mitral annular calcification (MAC) and systemic inflammation. The goal of the present study was to compare high-sensitivity C-reactive protein (hs-CRP) levels in patients with and without MAC and investigate the relationship between MAC and hs-CRP. Methods. One hundred patients with MAC who underwent transthoracic echocardiography (TTE) and 100 age-matched controls without MAC who underwent TTE were included in our study. Hs-CRP levels were compared between groups. Results. Prevalence of female gender, hypertension, and coronary artery disease were significantly higher in the MAC group than in the control group (64% versus 45%, P=0.007, 42% versus 28%, P=0.03 and 37% versus 18%, P=0.003, resp.). On multivariate analysis, age, gender, and coronary artery disease were the only independent predictors of MAC. The levels of hs-CRP were higher in the MAC group than in the control group (2.02±0.35 versus 1.43±0.47 mg/dl, P<0.001). This increase in hs-CRP levels in the MAC group persisted in patients without hypertension, coronary artery disease, and in male patients when compared to the control group. Conclusions. Our study demonstrated that hs-CRP, which is a sensitive marker of systemic inflammation, increased in patients with MAC.